Generation, Composition and Management of Municipal Solid Waste at Rudraprayag, Garhwal Himalaya - Sharma, S.; Prasad, C.; Singh, R.; Anuradha, -; Deep, A.; Kumar, R. (Journal of Scientific Research, 2021)
The key objective of the current research effort was to investigate the generation and composition of the municipal solid waste and to assess the recent management practices for solid waste management. The study area was divided into nine wards and four zones on the basis of population size, their economic and living standards. The total solid waste generation during the study period was around 4-5 tonnes per day. The qualitative solid waste analysis of Rudraprayag reveals that it includes the biodegradable, non-biodegradable and inert waste. However, the quantitative solid waste analysis reveals that the highest generation of biodegradable waste was found in February (89.16 %) and lowest in May (79.06 %). Non-biodegradable waste was recorded highest during March (25.72 %) and lowest during June (7.73 %). The percentage of inert waste was maximum during April (2.87 %) minimum during June (0.037 %). The total waste generation was found maximum during February which was 5883.983 g. However, it was found minimum during May which was 2596.034 g.